Infrared thermography based defect analysis of photovoltaic modules using machine learning - Mobin, Ovib Hassan; Tajwar, Tahmid; Khan, Fariha Reza; Hossain, Shara Fatema (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2020.